1995
DOI: 10.1002/1097-4679(199503)51:2<303::aid-jclp2270510222>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

The alcohol paradox: A psychological model

Abstract: The paradoxical continuation of excessive drinking by chronic alcoholics despite extremely aversive personal deterioration is addressed by a two‐factor theory. The theory regards the increasing stereotypy of alcohol‐related behaviors as a function of: (a) primary neuropsychological impairments that result from alcohol abuse and (b) secondary fears of catastrophic failure attendant upon brain dysfunction, which leads to acquired aversions to situations that require adaptive behaviors. A schematic quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…These findings support Goldman's (1990) postulated connection between the cognitive status of recovering individuals and their ability to effectively interact with others. These data are also consistent with Rosenbaum's (1990) formulation of the alcohol paradox —the fact that alcoholics continue to drink when this behavior increasingly worsens their quality of life. Rosenbaum suggested that the cognitive deficits incurred by the alcoholic limit his or her ability to process new information and to learn new responses.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…These findings support Goldman's (1990) postulated connection between the cognitive status of recovering individuals and their ability to effectively interact with others. These data are also consistent with Rosenbaum's (1990) formulation of the alcohol paradox —the fact that alcoholics continue to drink when this behavior increasingly worsens their quality of life. Rosenbaum suggested that the cognitive deficits incurred by the alcoholic limit his or her ability to process new information and to learn new responses.…”
Section: Discussionsupporting
confidence: 77%
“…Marital and family studies have shown that alcoholics often display interpersonal anger and hostility (Jacob & Krahn, 1988; Jacob, Ritchey, Cvitkovic, & Blane, 1981; Jacob & Selhammer, 1982; Leonard & Jacob, 1990; Rosenbaum, 1990). Two important components of relapse situations for alcoholics include conflictual interpersonal situations and negative affect (Marlatt & Gordon, 1982); these situations potentially mediate relapse to other drugs of abuse as well.…”
mentioning
confidence: 99%